A Dynamic Framework for Mass-Energy Interaction: Exploring the Role of Time and Relativity (London Journal of Research In Science: Natural and Formal, 2025)
The relationship between mass and energy is well-established, yet the behavior of mass when interacting with energy warrants further exploration. This study examines how the introduction of time into the mass-energy interaction influences the behavior of mass. Furthermore, it investigates whether the efficient utilization of energy could potentially enable travel at speeds exceeding that of light. This paper extends the conceptualization of energy by considering mass not as a static entity but as a dynamic quantity. It explores how mass distributes received energy and its behavior under various values of energy and time. The investigation begins with the fundamental form of mass, specifically the point energy mass, which is influenced by both energy and time. The study then expands to encompass larger and more complex forms of mass, analyzing the generalized effects of energy and time on their behavior. Additionally, the study examines the roles of space and speed in relation to energy and time, incorporating in the investigation fundamental equations of relativity. The findings suggest the possibility of mass traveling at speeds that would be considered as limited until now, by setting appropriate mass factors.